Improved breastfeeding with back massage among postnatal mothers - Widiastuti, Ni Made Rai; Widiani, Ni Nyoman Ayuk (International Journal of Research in Medical Sciences, 2020)
Background: The achieving target of exclusive breast milk in Indonesia has not been achieved. The unsuccessful approval of exclusive breastfeeding is partly due to the mother's reasons for the inadequacy of milk production. Physiologically, oxytocin and prolactin are responsible for the smooth production of breast milk. The release of the hormone oxytocin in addition to being transferred by stimulation to the nipple through the baby's mouth or through spinal massage. Application of back massage techniques or oxytocin massage to provide stimulation that is expected to increase patient comfort, prevent oxytocin release, and increasing milk production. Methods: This research is a quasi-experimental design with a time series design and a control time series design. The sample this study were 15 postpartum mothers treated group and 15 postpartum mothers in the control group. Data was collected by the method of intervention and direct observation on the frequency of urinating infants. Data analysis using repeated ANOVA test. Results: Based on the results of research on the frequency of urinating in the control group had an average of 5.6 and a treatment group of 6.9. This is reinforced by the value of p=0.0001 (p<0.005) which means that there is an effect of giving back massage to increase milk production in postpartum mothers. Conclusion: This study suggests that giving back massage techniques to postpartum mothers as an alternative to increase milk production in postpartum mothers and included as one of the basic care for postpartum mothers since the first day after childbirth.